Enhancement of the Second Harmonic Generation from WS2 Monolayers by Cooperating with Dielectric Microspheres. Issue 3 (5th December 2018) - Li, Xiaohong; Liu, Weiwei; Song, Yiling; Zhang, Cong; Long, Hua; Wang, Kai; Wang, Bing; Lu, Peixiang
Abstract: Herein, a 20‐fold enhancement of the optical second harmonic generation (SHG) from WS2 monolayers by cooperating with SiO2 dielectric microspheres (MSs) is reported. Detailed experiment and simulation studies indicate that the SHG enhancement is dominantly originated by the enhanced excitation intensity and enlarged collection efficiency produced by the SiO2 MSs. The size effect of the SiO2 MS on the SHG enhancement is also systematically investigated. Moreover, the SHG enhancement is found to be very sensitive to the surrounding refractive index of the SiO2 MS, which advocates great promise for the photonic sensing applications. This work provides a low‐cost and efficient approach to enhancing the SHG emission, and demonstrates great potential for functional nanodevices based on hybrid dielectric structures. Abstract : A 20‐fold enhancement of the optical second harmonic generation (SHG) from WS2 monolayers by cooperating with SiO2 dielectric microspheres (MSs) is reported. The SHG enhancement is attributed to the increased excitation intensity and enlarged collection efficiency produced by the SiO2 MSs. Moreover, a proof‐of‐concept photonic sensing application based on SHG is demonstrated.